1998
DOI: 10.1002/(sici)1096-9896(199803)184:3<283::aid-path25>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of T-helper secretory differentiation and types of antigen-presenting cells in squamous intraepithelial lesions of the uterine cervix

Abstract: This study addressed the notion that the progression of cervical cancer is associated with a T‐helper 2 (TH2) immunodeviation by analysing cytokine expression in 60 cervical biopsy specimens, spanning the spectrum from normal cervical tissue to high‐grade squamous intraepithelial lesions (SILs). The biopsies were analysed by immunohistochemistry for the expression of TH1 [interleukin‐2 (IL2), interferon gamma (IFNγ)] and of TH2‐type cytokines (IL4, IL6). Positive cells were usually observed in the subepithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0
5

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 40 publications
(34 reference statements)
3
68
0
5
Order By: Relevance
“…A number of recent publications has drawn attention to tumorinduced dysfunction of DC as a mechanism to escape immunosurveillance (3)(4)(5)(6)(7)(8)(9). Indeed, a reduced number of DC in primary tumors has been observed for breast cancer, basal cell skin cancer, cervical cancer, and colon cancer, among others (10). In addition, advanced cancer is associated with impaired differentiation and Ag-presenting functions of DC and their precursor cells (11).…”
Section: T He Importance Of Dendritic Cells (Dc) 2 In the Inductionmentioning
confidence: 97%
“…A number of recent publications has drawn attention to tumorinduced dysfunction of DC as a mechanism to escape immunosurveillance (3)(4)(5)(6)(7)(8)(9). Indeed, a reduced number of DC in primary tumors has been observed for breast cancer, basal cell skin cancer, cervical cancer, and colon cancer, among others (10). In addition, advanced cancer is associated with impaired differentiation and Ag-presenting functions of DC and their precursor cells (11).…”
Section: T He Importance Of Dendritic Cells (Dc) 2 In the Inductionmentioning
confidence: 97%
“…6,17,18 For example, we have observed that the density of LC is significantly reduced and the immunosuppressive cytokine IL10 is more frequently expressed in the microenvironment of TZ in comparison to the exocervix. 5,6,17 To the contrary, other groups have reported that the density of LC in the TZ is equal to that of the exocervix. 19,20 As an approach to understanding the factors involved in the initiation and progression of SILs, we sought to use a variety of methods to assess the differential density and the antigen presenting function of LC derived from TZ and SILs.…”
mentioning
confidence: 88%
“…For example, previous works have demonstrated that metaplastic areas are associated with a lower density of LCs. 9,10 Besides the communication of epithelial and immune cells by soluble factors, there also exist important cell-cell interactions. For example, the protein E-cadherin, which is critical for intercellular adhesiveness and maintenance of normal epithelial tissue architecture, is also involved in the homophilic and heterotypic interactions between epithelial cells and diverse cell types of the immune response, including LCs 11 and intraepithelial T lymphocytes (via ␣E␤7 integrin).…”
mentioning
confidence: 99%